Sleep quality of paramedics in the Czech Republic - Locihová, Hana; Kupčíková Břegová, Bohdana; Zittová, Renata; Hrušková, Jana; Bahulová, Monika (Kontakt, 2024)
Introduction: Sleep disorders are common among shift workers and those who work under stressful and unpredictable conditions. Sleep quality and its promotion in paramedics are understudied. Objective: The study aimed to investigate the quality of sleep in emergency medical service workers, to compare certain relationships between variables (gender, age, length of experience), and to assess whether a cut-off score of 10 is appropriate for the discriminatory ability of the selected instrument in the Czech clinical setting. Design: A cross-sectional study. Methods: Data were obtained using the Pittsburgh Sleep Quality Index (PSQI). The sample comprised 191 paramedics. Data were analyzed using selected statistical methods. Results: The mean PSQI total score was 7.45 (SD 3.60). The lowest scoring component was sleep duration (1.45; SD 1.01). There was no relationship between sleep quality and gender. With respect to age, two components, sleep disturbances and daytime dysfunction, were found to be significant (p < 0.05). Regarding the length of experience, daytime dysfunction was identified as a significant component. The PSQI total parameter with a cut-off of 10 (PSQI total ≤10 good sleep; PSQI total >10 poor sleep) was confirmed to be suitable for discriminating the subjectively perceived sleep quality in paramedics. Conclusion: The study demonstrates that sleep quality is compromised in paramedics. Impaired sleep quality has the greatest impact on daytime dysfunction in paramedics. The PSQI, with a cut-off score of 10, is an appropriate instrument for assessing their sleep disturbances.
Keywords: průzkumy a dotazníky; Surveys and Questionnaires; Sleep Disorders, Circadian Rhythm; zdravotničtí záchranáři; Humans; poruchy cirkadiánního rytmu (spánek); Česká republika; kvalita spánku; lidé; Czech Republic; Shift Work Schedule; Sleep Quality; Paramedics; práce na směny